1986
DOI: 10.1159/000146146
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Cultured Arterial Smooth Muscle Cells Growing on Cyclically Stretched Substrates

Abstract: Arterial smooth muscle cells from rabbit aortic media were grown in first subcultures on hydrophilized and collagen-coated silicone membranes which were then subjected to directional cyclic stretches and relaxations at a frequency of 50 times/min. The membranes were stretched 2, 5 and 10% beyond their resting length. Cells on unstretched and stationary membranes in the same chamber served as controls. The cells which were stretched with an amplitude of 2% remained in random orientation after 14 days of continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 12 publications
(12 reference statements)
7
70
1
Order By: Relevance
“…Mechanical stretching of SMCs cultured on distensible substrata or entrapped in collagen gels has been shown to have profound effects on SMC phenotypic state, [99][100][101][102][103][104][105][106]101,[106][107][108][109]9,96,[110][111][112][113][114][115][116][117][118][119] growth factor release, 120 -122 proliferation, 100,123,124 and vascular tone, 125,126 leading several groups to investigate these mechanisms as a means of enhancing the development and maturation of tissue-engineered arteries. In particular, Kanda et al showed that adult bovine SMCbased collagen MEs that were cyclically loaded at 1 Hz with a strain amplitude of 10% for up to 4 weeks exhibited increases in contractile components such as myofilaments, dense bodies, and basement membranes, 106 indicating that cyclic stretching induces SMC reversion to a more contractile phenotype.…”
Section: Cyclic Stretching/distension Of Constructsmentioning
confidence: 99%
“…Mechanical stretching of SMCs cultured on distensible substrata or entrapped in collagen gels has been shown to have profound effects on SMC phenotypic state, [99][100][101][102][103][104][105][106]101,[106][107][108][109]9,96,[110][111][112][113][114][115][116][117][118][119] growth factor release, 120 -122 proliferation, 100,123,124 and vascular tone, 125,126 leading several groups to investigate these mechanisms as a means of enhancing the development and maturation of tissue-engineered arteries. In particular, Kanda et al showed that adult bovine SMCbased collagen MEs that were cyclically loaded at 1 Hz with a strain amplitude of 10% for up to 4 weeks exhibited increases in contractile components such as myofilaments, dense bodies, and basement membranes, 106 indicating that cyclic stretching induces SMC reversion to a more contractile phenotype.…”
Section: Cyclic Stretching/distension Of Constructsmentioning
confidence: 99%
“…While there is no consensus regarding the specific response mechanism, it is thought that the cytoskeleton plays an important role in sensing the cell's physical environment (9,32,33). To study the cellular response to mechanical stresses, different methods have been used, including membrane strain studies (6,8,11,15,28,37,39,50) and cone viscometer experiments (49). More recently, new techniques have allowed greater control of the applied forces and the targeting of specific membrane receptors (1,5,12,21,23,35,42,47,48).…”
mentioning
confidence: 99%
“…3 Thus, the behavior of vascular cells such as ECs and SMCs cultured on stretchable substrates which were periodically stretched and relaxed is of interest and was analyzed by various investigators. 23,25,33,36,38,42,43,52,53 These studies have shown that vascular cells tend to align perpendicular to the direction of strain independently of their animal or tissue origin. This suggests that, irrespective of cellular species and tissue and irrespective of the usage of primary cells or non-vascular cell lines, mechanical stressinduced cellular alignment is a common behavior of adhesive cells in vitro, which may operate to induce cellular orientation in tissues in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…32 Several studies have shown that cells on uniaxial cyclically stretched substrates reorient themselves nearly perpendicular to the direction of strain [32][33][34][35][36][37][38][39][40][41] and that the actin cytoskeleton is reorganized perpendicular to the strain direction. [33][34][35]42 Cultured SMCs in vitro can be induced to reorient to a uniform perpendicular alignment into the direction of principal uniaxial mechanical strain. 16,41,43,44 The SMC orientation response is consistent with the response that has been found for many different cell types such as ECs, osteoblasts, fibroblasts, and melanocytes.…”
Section: Introductionmentioning
confidence: 99%